Development and validation of a pen side test for Rift Valley fever. - Catherine Cêtre-Sossah; Aurélie Pédarrieu; Mikael Juremalm; Petrus Jansen Van Vuren; Alejandro Brun; Ahmed Bezeid Ould El Mamy; Jean-Michel Héraud; Claudia Filippone; Jean-Pierre Ravalohery; Hassan Chaabihi; Emmanuel Albina; Laure Dommergues; et al. (Public Library of Science (PLoS), 2019)
Background Rift Valley fever (RVF) is one of the main vector borne zoonotic diseases that affects a wide range of ruminants and human beings in Africa and the Arabian Peninsula. A rapid and specific test for RVF diagnosis at the site of a suspected outbreak is crucial for the implementation of control measures. Methodology/principal findings A first-line lateral flow immunochromatographic strip test (LFT) was developed for the detection of the nucleoprotein (N) of the RVF virus (RVFV). Its diagnostic performance characteristics were evaluated using reference stocks isolates recovered from different hosts and in geographic regions mimicking clinical specimens and from known RVF negative serum samples. A high level of diagnostic accuracy (DSe (35/35), DSp (167/169)) was observed, including the absence of cross-reactivity with viruses belonging to different genera. Conclusion/significance The fact no specialized reagents and laboratory equipment are needed, make this assay a valuable, first-line diagnostic tool in resource-poor diagnostic territories for on-site RVFV detection, however the staff require training.